The effects of organic and inorganic fertilizer on the growth of Zoysia matrella and physico- chemical characteristics from steep slope - Shamsol Kamal, Nurul Husna (2015)
The objectives of the study were; 1) to investigate the short-term effects of fertilizers on soil physical and chemical characteristics; 2) to study the effect of soil treatments and plant species on the dry matter yield and root density and; 3) to identify the suitable plant species for controlling erosion on the steep slope. This study was conducted on the steep slope at Faculty of Agriculture, University Putra Malaysia with 5 treatments and 4 replications by using Randomized Completely Block Design (RCBD). The treatments were; treatment 1, without fertilizer (Control), treatment 2, NPK+ EFB (NEFB), treatment 3, NPK+ Biogreen EnergyTM (NBG), treatment 4, EFB + Biogreen EnergyTM (EFBBG) and treatment 5 was a combination of NPK+ EFB + Biogreen EnergyTM (NEFBBG). Based on the result, the combination of NPK+ EFB + Biogreen EnergyTM (NEFBBG) was showed the highest means value on soil porosity, soil pH, soil aggregate stability, soil leachates (phosphorus and potassium), available P in soil, and total carbon. So, the application of combination fertilizer showed a positive result on improving chemical and physical characteristic of soil. The organic fertilizer had showed significant result for Zoysia matrella’s growth development. As a conclusion, a combination of organic and inorganic fertilizer can give the best result as compared to the other treatments in this experiment.